The Importance of Principal Leadership Management in Increasing the Competence of Elementary School Teachers in Medan City, North Sumatra - Lisnasari, Srie Faizah; Karo Sekali, Pelista Br; Jainab, Jainab; Widiyarti , Gemala; Sidebang , Restio; Simbolon, Rinci (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
To leadership to the principal of the school plays an important role in improve the competence of teachers in their schools. Efforts to increase this are carried out by making policies that are translated into programs to increase teacher competency. This study aims to describe; (1) Principal Management in Improving Teacher Competence; (2) Principal Management Success in Increasing Teacher Competence; (3) Supporting factors, inhibiting factors and solutions for Principal Management in Improving Teacher Competence at SD N Medan City, North Sumatra. This research is in the form of qualitative research, the data collection method used is observation, interviews, and documentation. The research results show that Principal management in improving teacher competence, namely : (1) Involving teachers in training, training and seminars, (2) Implementation of supervision (3) Prioritizing discipline, (4) Motivating teachers. Application of leadership management school principals in improving teacher competence greatly affect the competence of teachers in SD N Medan City, North Sumatra, namely that the teachers have started apply the basic competency standards regulated by the government as well as possible. In implementing the program there will be supporting factors, inhibiting factors and leadership management solutions principal in improving teacher competence in Elementary School Medan City, North Sumatra.